Addressing the hydrogen entrapment in Al2024 alloys using scanning transmission electron microscopy and density functional theory - Florent Ravaux; Muhammad Sajjad; Humaira Zafar; Mohamed E. Daoud; Helen Kamoutsi; Cyril Aubry; James Weston; Nirpendra Singh; Gregory Haidemenopoulos; Dalaver H. Anjum (Journal of Alloys and Metallurgical Systems, 2023)
The effect of precipitate coherency in an aged aluminum (Al) 2024 alloy is investigated using scanning transmission electron microscopy (STEM) and density functional theory (DFT) methods. The focus of the study is on understanding the effects of hydrogen (H2) entrapment in the alloy, which leads to the degradation of its corrosion resistance. We employed STEM to analyze the structure and strain properties of the alloy at high spatial resolution. This has been achieved by applying the geometrical phase analysis (GPA) to the acquired HRSTEM images. The determination of strain field around the precipitates was utilized to gauge the degree of coherency at the interface of the precipitates with Al matrix. We also applied density functional theory (DFT) simulations to investigate the interfacial energy at the interfaces of the precipitates with the Al matrix. The obtained results of the DFT simulations showed that the interfacial energy at the semi-coherent precipitates was determined to be 0.06 eV per atom, which was higher compared to the coherent precipitates. Our findings suggest that the semi-coherent precipitates have a less stable interface with the Al matrix. Furthermore, the study revealed that the H2 entrapped at the semi-coherent precipitate regions exhibits a binding energy which is 3.2 eV lower than that of the coherent precipitates. This implies that hydrogen binds more strongly at the semi-coherent precipitate cites, which enhances the process of the alloy embrittlement.